ECOCIDE RUSSIA AND THE TASKS OF VOCATIONAL EDUCATION IN THE ENVIRONMENTAL POST- WAR DEVELOPMENT OF THE AGRARIAN INDUSTRY (Innovative professional education, 2024)
Environmental problems that arise as a result of Russia's armed aggression in Ukraine are the disruption of natural ecosystems, the destruction of  environmentally hazardous industrial facilities, thedeterioration of the sanitary and hygienic indicators of drinking water, the disruption of nature conservation areas, the threat of chemical and radioactive pollution. The solution to the problem of post-war reconstruction is to train a competitive specialist who has solid ecological knowledge about the environment, who is able to ensure the ecological post-war recovery of the agricultural sector and carry out environmental protection and environmentalactivities at his workplace in the context of the concept of sustainable development.
Keywords: environmental crime, man-made disaster, eco-oriented learning technologies, environmental education